Pump Speed Waveform Analysis to Detect Aortic Valve Opening in Patients on Ventricular Assist Device Support. Issue 8 (August 2015) - Hayward, Christopher; Lim, Choon Pin; Schima, Heinrich; Macdonald, Peter; Moscato, Francesco; Muthiah, Kavitha; Granegger, Marcus
Abstract As the aortic valve (AV) opens, the pump pressure head remains constant, which is reflected as a "notch/plateau" in pump pressure and flow signals. However, instantaneous flow estimation may be influenced by friction and is particularly difficult in axial pumps. Therefore, a new method to determine the duration of AV opening based on the area under the curve (AUC) of the power spectral density analysis of pump speed signal was developed. Data from patients implanted with HeartWare HVAD left ventricular assist device were studied at different pump speeds, with simultaneous transthoracic echocardiography in two cohorts. In the first group, pump data of 15 patients were used to investigate the ability to discriminate between an open and closed AV. In the second cohort of a further 13 patients, the duration of AV opening was measured from digitized M‐mode images, and the relationship between the AV opening time and the new method assessed. In 14 of the initial 15 patients, AV status could be discriminated using only one threshold for all patients. In the second cohort, gradual speed reduction resulted in aortic valve opening in 12 of the 13 patients. The correlation between AV opening duration and AUC was 0.96 ± 0.03. Regression analysis indicated a linear relationship in each of the patients with a small error between the fit and the measured opening time (root mean square error = 11.0 ± 7.6 ms). However, the slopes (69.0 ± 52.8) and intercepts (−31.4 ± 78.0) varied widely between patients. The sensitivity and specificity for the new method using AUC threshold of 0.95 for aortic valve closure was 95% and 91%, respectively. The newly developed method to detect AV opening not only provides information on the AV status during LVAD support (open/closed) but also gives insight into the duration of AV opening. Because the slope of the relationship varies from patient to patient, initial training and adaptation of the method to each patient seems to be required.